Biofilmes gerados a partir da saliva de crianças sem e com cárie na primeira infância: resposta ao desafio cariogênico e correlação com os de suas mães - Azevedo, Marina Sousa (2010)
Micro-organisms belonging to the resident oral microflora are organized into complex communities, the biofilms, and are the direct cause of the caries process. It is necessary to understand the degree to which biofilm physicochemical and nutrient environments affect the plaque development in individuals differing in their oral environments. In this context, microcosm biofilm models could be used to answer specific questions related to caries. The aim of this study was to test the hypothesis that microcosm biofilms growth from inoculums of caries free children (CF), childrenwith early childhood caries (ECC) and with severe early childhood caries (S-ECC) would provide the same cariogenic response under regular sucrose exposure. Also, microcosm biofilms formed from saliva of children and their mothers considering cariogenic response and microbiota composition were compared. Three children of each group were selected: CF, ECC and S-ECC and their mothers. The mother-child pairs were examined and the dental status was recorded. Saliva samples were collected and screened for microbial composition. Microcosm plaque biofilms were initiated from saliva, growth on bovine enamel discs in artificial saliva enriched with mucin (DMM) for up to 10 days in 24-well microplates under anaerobic conditions. Biofilms were growth with and without sucrose under a semi-dynamic regimen previously tested. DMM was replaced daily and pH measurements were recorded for DMM with sucrose or DMM without sucrose supernatants.On the 10th day, biofilms were collected and microbiota composition was assessed by culture methods. The enamel mineral loss was obtained by the percentual surface microhardness change (%SHC) for each enamel disc. The relationship between outcome variables (pH, microbiota and %SHC) from mothers and children was estimated by Spearman s correlation test, considering each outcome within each caries risk group. Independent statistical comparisons among surface microhardness change, pH and biofilm microbiota were made for group and condition (sucrose exposure) and analyzed using 2-way ANOVA followed by Tukey s test. Values of p ≤ 0.05 were considered significant. The groups with cariogenic challenge condition showed: higher levels of the total aciduric counts, S. mutans and total oral lactobacilli, lower value of pure DMM pH and a higher mineral loss than the group without cariogenic challenge. Differences between groups (CF, ECC and S-ECC) could not be seen, except for DMM pH with sucrose for children (p=0.005) and for pure DMM pH (p=0.004) and for total aciduric counts (p=0.037) for mothers. A correlation was found between microcosm biofilms generated from children and their mothers inoculums under cariogenic challenge. Therefore, within the limitations of this study, it is possible to conclude that microcosm biofilms growth from inoculums of children with or without severe ECC provide similar cariogenic response under regular sucrose exposure. Moreover, cariogenic challenge was crucial to correlatecariogenic response of microcosm biofilms between the inoculum of mothers and their children